1998
DOI: 10.1016/s0194-5998(98)70267-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Tracheoesophageal Voice after Pectoralis Major Flap Reconstruction of the Neopharynx

Abstract: Although tracheoesophageal voice restoration is accepted after reconstruction of the neopharynx with the pectoralis major myocutaneous flap, the character of such voice is not well described. Six patients reconstructed with the pectoralis major flap after laryngopharyngectomy underwent successful voice restoration with the Blom-Singer prosthesis. Voice was evaluated by a standardized protocol and compared with voices of control subjects treated with total laryngectomy and similar voice restoration. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
(42 reference statements)
2
16
0
Order By: Relevance
“…There is no difference in dynamic extension in patients submitted to reconstruction of the pharynx with flaps 20 . What has been observed is that different types of prostheses [2][3][4][5][6][7] and the manner of stoma occlusion 3,5,7 influence dynamic extension.…”
Section: Correlation Of Intraluminal Esophageal Pressure With the Dynmentioning
confidence: 91%
“…There is no difference in dynamic extension in patients submitted to reconstruction of the pharynx with flaps 20 . What has been observed is that different types of prostheses [2][3][4][5][6][7] and the manner of stoma occlusion 3,5,7 influence dynamic extension.…”
Section: Correlation Of Intraluminal Esophageal Pressure With the Dynmentioning
confidence: 91%
“…This finding is significant clinically because poor speech quality in children has been demonstrated to have a negative influence on the perception the listener has of the individual [19,20]. The results of perceptual analysis such as were performed in our study of children with RRP provide clinicians with a baseline of voice quality and a way to monitor the course of therapy to improve voice quality [21][22][23].…”
Section: Perceptual Evaluationsmentioning
confidence: 71%
“…Deschler et al [38] reported perceptual differences (but not acoustic) between patients undergoing standard laryngectomy and those who had pectoralis flap reconstruction, raising the possibility that other differences may be present. The limited number of TL+PM speakers (n = 4), however, precluded more detailed statistical analysis.…”
Section: Resultsmentioning
confidence: 99%